2001
DOI: 10.1097/00129492-200105000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Ossiculoplasty: A Statistical Staging System

Abstract: The revised staging system, the Ossiculoplasty Outcome Parameter Staging Index, more adequately predicts hearing outcome in this series of 200 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
6
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(211 citation statements)
references
References 11 publications
11
182
6
12
Order By: Relevance
“…15 Whereas, in a multivariate analysis by Yung, the results predicted that those with present malleus were 6.36 times more likely to be successful. 16 We also observed that in more than half (66%) of the patient, incus was either necrosed or lost.…”
Section: Ossicular Involvement and Air -Bone Gapmentioning
confidence: 94%
“…15 Whereas, in a multivariate analysis by Yung, the results predicted that those with present malleus were 6.36 times more likely to be successful. 16 We also observed that in more than half (66%) of the patient, incus was either necrosed or lost.…”
Section: Ossicular Involvement and Air -Bone Gapmentioning
confidence: 94%
“…[17][18][19] These include revisions versus one stage surgeries. 12,18,20 The presence or absence of cholesteatoma was considered to contribute to the results of Ossiculoplasty. In the present study, the CSOM patients with Cholesteatoma were 45 (62.5%) and all these surgeries were done as a single stage operation.…”
Section: Discussionmentioning
confidence: 99%
“…SPITE (surgery, prosthesis, infection, tissues, and eustachian tube), OOPSI (ossiculoplasty, outcome, parameter staging index), and middle ear risk index are some of the proposed methods [4,10,11] .…”
Section: Discussionmentioning
confidence: 99%